Strip Till Age of Soil for Deuteric Sowing (Second Crop) - Nasritdinov Akhmadzhon Abdukhamidovich; Muhabbat Davlatova Urmanovna; Numonov Otabek Urmonovich (Research Parks Publishing LLC, 2021)
According to the test results, a section of the working bodies of strip tillage for re-sowing was selected, the parameters of the height, length of the soil-shifting plate of its flat-cutting paw and the angle of attack of the discs were experimentally determined.